A Rare Case of Eosinophilic Gastroenteritis and Ampullitis Leading to Benign Papillary Stenosis - Akwe Nyabera; Keya Shah; Nso Nso; Saphwat Eskaros; Negar Niknam (Case Reports in Gastrointestinal Medicine)
Eosinophilic gastroenteritis is characterized by eosinophilic infiltration of the gastrointestinal wall. There have been limited studies of eosinophilic infiltration involving the ampulla. We present a 70-year-old woman with a history of asthma, eosinophilic esophagitis, and eosinophilic sinusitis, who underwent work up for postprandial abdominal pain and abnormal liver function tests. The patient had various imaging studies done, including computed tomography (CT) scan, magnetic resonance imaging (MRI), and magnetic resonance cholangiopancreatography (MRCP). Dilated extrahepatic bile duct with distal tapering towards the ampulla was noted on MRCP and afterwards on endoscopic ultrasound (EUS). Endoscopic retrograde cholangiopancreatography (ERCP) revealed an inflamed major ampulla with benign papillary stenosis. The patient was treated with sphincterotomy, sphincteroplasty/dilation of distal common bile duct, and placement of an 11.5 Fr × 7 cm plastic stent into the bile duct. Additionally, she was started on prednisone, which was gradually tapered down. The patient demonstrated significant improvement with systemic steroid therapy. Liver function tests (LFTs) completely normalized after ERCP. Ampullitis leading to papillary stenosis secondary to eosinophilic infiltration of the major papilla is a rare manifestation of eosinophilic gastrointestinal disorders (EGIDs). Early diagnosis would lead to appropriate medical and endoscopic management.